Protein engineering of human properdin - Higgins, J (1994)
﻿ Properdin is a serum glycoprotein that upregulates the alternative pathway of complement by stabilizing the C3bBb complex. It also binds sulphated glycoconjugates, such as sulphatide, in vitro. Properdin is composed of cyclic dimers, trimers and tetramers of a 53 kDa monomeric subunit. The monomer contains an N-terminal region of no known homology and six thrombospondin type 1 repeats (TSRs) of approximately sixty amino acids. The sixth TSR of properdin contains an insertion of approximately 30 amino acids which corresponds to the position of an intron in the human properdin gene. In order to identify the regions of properdin important for function, human properdin, and mutant forms each lacking a single TSR, were expressed in Chinese Hamster Ovary cells. In addition, limited tryptic digestion yielded "nicked" properdin by the cleavage of one peptide bond in TSR5. The structural and functional properties of the normal and altered forms of properdin were investigated. Wild type recombinant properdin is similar to properdin purified from plasma in size, immunoreactivity, N-terminal sequence, possession of N-linked sugar, oligomerization (as determined by electron microscopy and gel exclusion chromatography), and functional activity in an alternative pathway haemolytic assay, and in C3b and sulphatide binding assays. Properdin "nicked" in TSR5 is unable to bind C3b, while retaining its overall structure and its ability to bind sulphatide. The removal of TSRS prevents C3b and sulphatide binding. Properdin lacking TSR4 is unable to stabilize the C3bBb complex, but is able to bind C3b and sulphatide, and shows the presence of monomers and dimers in the electron microscope. Properdin without TSR3 is able to stabilize the C3bBb complex, to bind CSb and sulphatide, and forms dimers, trimers and tetramers. Properdin lacking TSR6 is unable to form oligomers. The N-linked carbohydrate of properdin is not required for oligomerization or stabilization of the C3bBb complex. Monoclonal antibodies which bind to the N-terminal region, TSR1, or TSR2 are able to inhibit properdin binding to CSb. A monoclonal antibody which binds TSR4 is able to inhibit properdin binding to sulphatide, but not to CSb. The results confirm that TSRs are folded as independent units. The N-terminal end and TSR5 of properdin are implicated in CSb binding. The vertices of properdin oligomers may be important for interaction with CSb. TSR4 may also be involved in stabilization of the C3bBb complex. The sulphatide binding site is distinct from the CSb binding site, but TSR5, which contains many basic residues, may be important for both activities.